Determination of the relationship between the Los Angeles abrasion values of aggregates and concrete strength using the Response Surface Methodology - Tunc, Esra Tugrul; Alyamac, Kursat Esat (Elsevier Sci Ltd, 2020)
The present study aims to determine the relationship between aggregate abrasion strength and concrete strength considering water-to-cement and aggregate-to-cement ratios. For this purpose, concrete mixtures with different water-to-cement ratios (0.38, 0.40, 0.42, 0.45, 0.50, 0.55 and 0.60) were prepared with different aggregate types (basalt, marble, limestone, and natural aggregates). Hardened concrete properties of the prepared specimens were determined. Also, the abrasion tests were performed for each aggregate used in the experiments to determine the Los Angeles abrasion values of the aggregates. Using the experimental data, the compressive strength and splitting tensile strength values of the concrete specimens with dimensionless parameters such as water-to-cement ratio, aggregate-to-cement ratio, and Los Angeles abrasion loss value were analyzed using the Response Surface Methodology. Thus, two new models were developed with a multi-purpose optimization method. The compressive strength and splitting tensile strength can be calculated with high accuracy for different mixture designs with these models using the aggregate abrasion loss value, water-to-cement ratio, and aggregate-to-cement ratio. In conclusion, savings in labor and time, and economic profit are expected by designing a concrete mixture in this way. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Concrete strength; Los Angeles abrasion loss; Response Surface Methodology; Aggregate; Water-to-cement ratio